Efficacy and safety of avacopan in antineutrophil cytoplasmic autoantibody-associated vasculitis: a retrospective cohort study in Japan - Genri Tagami; Makoto Yamaguchi; Hirokazu Sugiyama; Hiroshi Kinashi; Kentaro Imai; Keisuke Kamiya; Takayuki Katsuno; Takahiro Imaizumi; Shogo Banno; Yasuhiko Ito; Takuji Ishimoto (BMC Rheumatology)
Abstract Background Avacopan, an oral C5a receptor antagonist, demonstrated efficacy as an alternative to glucocorticoid therapy in patients with antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) in the phase 3 ADVOCATE trial. However, limited real-world data exist on the outcomes and experiences associated with avacopan use for AAV in Japan. Methods We performed a single-centre retrospective analysis and evaluated 21 patients with newly diagnosed or relapsed AAV who received avacopan. The co-primary outcomes were clinical remission at 6 and 12 months. Results Among the 21 patients, 20 (95.2%) achieved clinical remission at 6 months, and 19 (90.4%) sustained remission at 12 months. The median time from initiation of immunosuppressive therapy to the start of avacopan was 12 days (interquartile range, 5–26). Adverse events were reported in 10 patients (47.6%), with elevated liver enzyme levels observed in eight patients (38.1%) as the most frequent complication. Avacopan was discontinued in nine patients (42.9%). Despite early discontinuation, these patients achieved comparable rates of clinical remission at 6 months, sustained remission at 12 months, and experienced a reduction in glucocorticoid doses relative to those who continued avacopan. Conclusions A high incidence of adverse events, particularly liver enzyme elevation, and frequent early discontinuations of avacopan were observed. Nevertheless, favourable clinical outcomes and reduced glucocorticoid doses were achieved regardless of avacopan discontinuation. Further studies are warranted to validate the optimal use of avacopan in clinical practice.